On asymptotic behavior of solution to a nonlinear wave equation with space-time speed of propagation and damping terms (2021)
In this paper, we consider the asymptotic behavior of solution to the nonlinear damped wave equationutt − div¡a(t, x)∇u¢+ b(t, x)ut = −|u|p−1u t ∈ [0, ∞), x ∈ Rn u(0, x) = u0(x), ut(0, x) = u1(x) x ∈ Rn with space-time speed of propagation and damping potential. We obtained L2 decay estimates via the weighted energy method and under certain suitable assumptions on the functions a(t, x) and b(t, x). The technique follows that of Lin et al.[8] with modification to the region of consideration in Rn. These decay result extends the results in the literature.